Frivillige organisationers resocialiserende arbejde i Kriminalforsorgens institutioner - Annette Olesen; Anders Brinck Rosenholm (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Outsourcing in the criminal justice system is experiencing growth in the not-for-profit sector in many Western countries. There is, however, no indication of this trend in the Danish Prison and Probation Service. On the contrary, the collaboration between the penal voluntary sector and the Danish Prison and Probation Service is not formalised and knowledge about the penal voluntary sector in Denmark is scarce. This article uses original empirical data to map out the delivery of rehabilitative programmes by the penal voluntary organisations within prison and probation facilities. It also addresses the challenges and potentials of the informal collaboration between the Danish Prison and Probation Service and the penal voluntary  sector.